India: Agronet.com - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Agronet.com is a portal to agricultural resources for the entire agricultural sector - news, market updates, technology, services, organizations and companies, as well as seed for sale, tips, and links for farmers. In English and Hindi.